Evaluation of Quality Control in Clinical Chemistry Using Sigma Metrics - Njeru, Caroline; Amayo, Angela (My University, 2022)
Introduction: Six sigma improves the quality of outputs by analyzing and abolishing the source of defects and reducing variability in the manufacturing industry. It can be used as a self -assessment tool for laboratories when making their quality control frequency and strategy. Clinical laboratories tests with low sigma values (< 3σ) indicate that the analytical quality of the lab needs to be improved. Aim: The aim of the study was to evaluate clinical chemistry laboratory performance using six sigma metrics to improve quality. Materials and methods: Five parameters from renal and liver function tests were studied over a period of 6 months (Dec 2016-May2017). Data from IQC and EQA participation was used. The analytes were plasma creatinine, aspartate transaminase(AST), alanine transaminase(ALT), total serum protein, total and direct bilirubin. Sigma metrics was calculated using total allowable error as per CLIA recommendations. Bias was calculated from HUQAS EQA participation while coefficient of variation was calculated from IQC data collected during the above mentioned months. Results: Clinical chemistry had sigma metrics below 3, the highest sigma value was 2.01 while the lowest sigma value was 0.85. Conclusion: Clinical chemistry analytes had sigma levels less than 3, method performance improvement with stringent internal quality control and correct setting of control limits need to be applied. Application of sigma metrics in addition to daily internal quality control can identify analytical deficits and improvement in clinical laboratories